2014 International Conference on Indoor Positioning and Indoor Navigation (IPIN) 2014
DOI: 10.1109/ipin.2014.7275471
|View full text |Cite
|
Sign up to set email alerts
|

LED-tracking and ID-estimation for indoor positioning using visible light communication

Abstract: We are focusing our research on indoor positioning technology; specifically, a type that uses Visible Light Communication (VLC); modulatable LED lights transmit data at 9600 bps, using 4 Pulse Position Modulation (4PPM), while a fisheye lens-equipped camera receives the light signal over a 160degree field-of-view. This type of lighting requires neither additional space nor -power. We assigned a unique ID to each LED, in order to recognize its position. Self-location is calculated from the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Nakazawa et al presented [41] a VLP system with LED tracking. The authors used a fisheye-lens-equipped camera with 160 • FOV.…”
Section: Camera-based Vlpmentioning
confidence: 99%
“…Nakazawa et al presented [41] a VLP system with LED tracking. The authors used a fisheye-lens-equipped camera with 160 • FOV.…”
Section: Camera-based Vlpmentioning
confidence: 99%
“…The study reported an accuracy of 0.06 m when the receiver was moving at an average speed of 1.3 m.s1 in a room with dimensions 5×4×3 m3. The work in [13] utilises a fish-eye lens camera in conjunction with the Levenberg–Marquardt algorithm to estimate the receiver position with an accuracy better than 0.01 m. The authors in [14] carried out a comparative study of a Kalman filter and sequential importance sampling particle filters for positioning and tracking by measuring the RSS. The study concluded that the particle filter outperformed the Kalman filter at the expense of additional computational complexity.…”
Section: Introductionmentioning
confidence: 99%
“…A promising alternative solution is to utilize an image sensor (IS) as the receiver [14]- [18]. Work [17] employs a camera equipped with a fish-eye lens to capture more reference lights and improve the positioning accuracy.…”
Section: Introductionmentioning
confidence: 99%